Optimalisasi Metode Participatory Rural Appraisal (PRA) dalam Mengubah Perspektif Remaja terhadap Pernikahan Dini dan Meningkatkan Kesadaran akan Pentingnya Pendidikan Tinggi - Hidayat, Nauval Edghina; Dewi, Rismala; Kusumaningrum, Alya; Widjaya, Malik Wisnu; Syafiqurosyid, M. Zufar; Wardah, Nabila Amalya; Abriyanto, Abriyanto; Andriani, Adinda Viviana; Afif, Ahmad Ainul; Jayanti, Reny Dwi; Fridayani, Helen Dian (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Child marriage remains a significant social issue in Indonesia, including in the Imogiri area of Bantul Regency, which faces a dual challenge of high rates of marriage dispensation and low interest among adolescents in pursuing higher education. So, this community service program aims to enhance human resource quality in Jetis Hamlet, Selopamioro Village, Imogiri District, Bantul Regency through education and community empowerment, particularly in preventing early marriage and increasing interest in higher education. Early marriage remains a challenge in this region due to social and economic factors, as well as a lack of awareness about the importance of education. This program adopts the Participatory Rural Appraisal (PRA) method, actively involving the community in problem identification, discussions, outreach, monitoring, and evaluation. The main activities include raising awareness about the negative impacts of early marriage, providing counseling on career pathways, and offering information on access to higher education and scholarships. The results of the program indicate an increased awareness among community members regarding the consequences of early marriage and the significance of higher education. Participants demonstrated improved understanding after attending the outreach sessions, particularly concerning the risks of early marriage and the benefits of continuing education. Additionally, a shift in attitude towards early marriage was observed, with more participants expressing an interest in pursuing higher education compared to before. Evaluation using pre-test and post-test assessments indicated a significant improvement in participants' understanding and attitudes toward the topics presented. Thus, this program successfully created a positive impact by raising awareness and broadening the perspectives of the Jetis Hamlet community on the importance of education as a strategic measure to prevent early marriage and improve their future well-being